OPTIMIZATION OF THE COMPOSITION OF THE MIXTURE IN THE PRODUCTION OF POLYMER-COMPOSITE MATERIAL USING THE METHOD OF MATHEMATICAL PLANNING - Kasimov Akhtam Akromovich; Tashpolatov Salih Shukurovich; Sadiqova daughter of Feruza Abdulkhay (Scholars Digest Publishing, 2023)
This article analyzes the method of ensuring the operational properties of parts using a new polymer composite material for workers in the construction industry.
Keywords: polymer-composite material